Differences Growing Media In Autopot Fertigation System And Its Response To Cherry Tomatoes Yield - Nurpilihan Bafdal; Sophia Dwiratna; Dwi Rustam Kendarto (Universitas Padjadjaran, 2017)
Hydroponic cultivation system is one solution to overcome the limited agricultural land. This farming system is widely used in farming high-value horticulture, one of them is a cherry tomato plants. The key to success in the hydroponic system is the management of water and nutrients appropriate to the needs of plants. Nevertheless, fertigation system on hydroponic plant cultivation requires a fairly high production costs and dependent on electrical energy for circulation. This study aims to assess the application of fertigation systems that do not use electricity for the circulation of water and nutrients using autopot technology. Fertigation system using this autopot applied to the cherry tomato plants using three combinations of planting medium is husk-compost, husk charcoal-humus and husk-cocopeat with a ratio of 50%: 50%. The results showed that autopot system capable of supplying the needs of water and plant nutrients to the level of irrigation efficiency is very high also minus consumption of electrical energy. The combination of growing media and compost husk cherry tomato plants to respond favorably with yields of 4.72 kg/plant. Keywords : Hydroponics; Autopot technology; Growing media; Cherry tomatoes; Fertigation automation